One year outcome of structured diabetes mellitus educational program (SDEP) on the management of diabetes in a primary care clinic - Kamaruzaman, Nor Azam; Bakar, Mohd Bustamanizan; Z, Asyikin; Pasi, Hafizah (2020)
Health education is an integral part of patient centered care in diabetes mellitus as it may empower the patient in self management. The long term outcome of a structured diabetes educational program on the participants from a primary health clinic at Pekan, Pahang was studied. SDEP in targeted population is beneficial for diabetes control without the need for intensification of therapy.